Correlation of copeptin with osmolarity and electrolytes in diabetes Mellitus: A tertiary center outpatient experience. - Noor, Tooba; Kiran , Zareen; Ali , Arif; Syed, Sadiqa B; Hanif , Farina (International Journal of Endorsing Health Science Research, 2022)
Background: Arginine Vasopressin (AVP) plays a significant role in the pathophysiology of Diabetes Mellitus (DM) and its related nephropathy. Timely detection of copeptin, a surrogate biomarker of AVP, would help in minimizing the osmoregulatory complications secondary to DM. The study aimed to correlate serum copeptin levels with serum osmolarity and electrolytes in subjects with progressive stages of DM. Methodology: A total of 120 patients were recruited as controls, pre-diabetes, DM without nephropathy, and nephropathy. Serum copeptin levels were measured by Enzyme-Linked Immunosorbent Assay. At the same time, routine biochemical tests for diabetes and renal function were done from the affiliated diagnostic laboratory. Results: The mean copeptin and osmolarity levels were 207.74 ± 192.08 pg/ml and 302.29 ± 18.13 mOsm/kg, respectively. Both, the copeptin and osmolarity levels raises progressively from controls to various stages of DM and share significant positive correlation (r=0.214, p=0.019). Osmolarity was also correlated significantly with RBS (r=0.262), BUN (r=0.844), Na+ (r=0.210) and K+ (r=0.461). Conclusion: The significant correlation of copeptin with osmolarity highlights the importance of the AVP system in regulating body fluid equilibrium in diabetic patients progressing towards nephropathy. Timely detection of copeptin can play an important role in the early management of the disease.